Differentiation reprogramming in gastric intestinal metaplasia and dysplasia: role of SOX2 and CDX2. Issue 3 (10th November 2014) - Camilo, Vânia; Garrido, Mónica; Valente, Pedro; Ricardo, Sara; Amaral, Ana Luísa; Barros, Rita; Chaves, Paula; Carneiro, Fátima; David, Leonor; Almeida, Raquel
<x xml:space="preserve">Abstract</x> Aims Intestinal metaplasia (IM), which results from de‐novo expression of CDX2, and dysplasia are precursor lesions of gastric cancer that are associated with an increased risk for cancer development. There is much evidence suggesting a role for the transcription factor SOX2 in gastric differentiation. The aim of this study was to attempt to establish the relationship of SOX2 with CDX2 and with the differentiation reprogramming that characterizes gastric carcinogenesis, to assess their involvement in IM and dysplasia. Methods and results Characterization of gastric (SOX2, MUC5AC, and MUC6) and intestinal (CDX2 and MUC2) markers in normal gastric mucosa, in 55 foci of IM and in 26 foci of dysplasia, was performed by immunohistochemistry. SOX2 was expressed in the normal gastric mucosa, in the presumptive stem cell compartment, and was maintained in 7% of the complete (MUC5AC‐negative) and 85% of the incomplete (MUC5AC‐positive) IM subtypes. Twelve per cent of the dysplastic lesions expressed SOX2, and the association with MUC5AC was lost. CDX2 was present in all IMs and dysplastic lesions. Conclusions SOX2 is associated with gastric differentiation in incomplete IM and is lost in the progression to dysplasia, whereas CDX2 is acquired de novo in IM and maintained in dysplasia. This suggests that the balance between gastric and intestinal differentiation programmes impacts on the gastric carcinogenesis cascade progression.